Accounting the individual-typological profile in the competitive activity of hockey players of various game roles - Novakovskiy S.V; Kachalov D.V.; Machaidze E.; Kondratovich S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determination of the level of significant individual-typological components of the playing role of hockey athletes aged 14 years, influencing the effectiveness of competitive activity. Methods and structure of the study. An experimental study was conducted to assess the individual typological characteristics of 14-year-old athletes of various playing roles that are significant in hockey. The composition of the methods is determined by the specifics of sports activity and was aimed at diagnosing parameters that are significant for hockey athletes: the level of self-esteem, situational and personal anxiety, reaction speed and processing of visual information, mental stability and personality orientation, degree of endurance of the nervous system, accuracy and concentration, type temperamental characteristics. The study population consisted of young men born in 2010 who play hockey - members of the U-14 Ural Federal District national team, winners of the 2023 Federal District National Team Championship (n=25 people). Results and conclusions. Based on the identified level of selected indicators, individual typological profiles were compiled, presented in the form of psychograms.